Evaluation of Stress and Associated Biochemical Changes in Patients with Type 2 Diabetes Mellitus and Obesity - Tyagi K (Dove Medical Press, 2021)
Kanchan Tyagi,1 Nidhi Bharal Agarwal,2 Prem Kapur,3 Sunil Kohli,3 Rajinder K Jalali4 1Department of Pharmaceutical Medicine, School of Pharmaceutical Education and Research, Jamia Hamdard, New Delhi, 110062, India; 2Centre for Translational and Clinical Research, School of Chemical & Life Sciences, Jamia Hamdard, New Delhi, 110062, India; 3Hamdard Institute of Medical Sciences and, Research, HAH Centenary Hospital, New Delhi, 110062, India; 4Physician and Healthcare Consultant. Formerly, Sun Pharmaceuticals Industries Limited, Gurgaon, 122015, IndiaCorrespondence: Nidhi Bharal AgarwalCentre for Translational and Clinical Research, School of Chemical & Life Sciences, Jamia Hamdard, New Delhi, 110062, IndiaTel +91 9818334770Email nidhi.bharal@gmail.comPurpose: Type 2 diabetes mellitus (T2DM), a metabolic disorder, remains associated with a physiological impairment affecting large populations worldwide. Onset of T2DM is multifactorial where obesity and abnormal basal metabolic rate are considered most critical. Of people diagnosed with T2DM, about 80% are also obese. It is also reported that obese individuals have an increased odds of developing depression, whereas T2DM is estimated to increase the incidence by two-fold. The preponderance of research data demonstrates that T2DM alters the serum level of cortisol and adiponectin which are known to be associated with neuronal physiology. The study explored, how a metabolic disorder like T2DM is linked with the altered plasma level of cortisol and adiponectin, the risk factors for stress and depression.Patients and Methods: A cross-sectional population study was conducted in T2DM patients using a bimodal approach. First approach used questionnaires, (1) Patient Health Questionnaire (PHQ-9) and (2) Stress Coping Inventory Questionnaire (SCQ) to assess signs and symptoms of depression and stress, respectively, in T2DM patients. In the second approach, robust biochemical analysis was conducted for serum adiponectin and cortisol levels.Results: An association of T2DM in stress and depression was evaluated in 158 subjects (105 T2DM obese patients and 53 healthy controls). A lower PHQ-9 score and adiponectin levels were seen in T2DM obese patients compared to healthy controls (p< 0.05). Further, results also depicted a lower adiponectin levels in T2DM obese patients with depression compared to T2DM obese patients without depression (p< 0.05). The study did not find a significant difference in cortisol serum levels among the T2DM and control groups. However, a higher level of serum cortisol was reported in T2DM obese patients with depression over those T2DM obese patients who lacked depression (p< 0.05).Conclusion: The findings suggest that T2DM obese patients might have a higher risk of developing stress and depression. Further, biochemical parameters, adiponectin and cortisol, might be the potential biomarkers for T2DM and may help in early diagnosis of these comorbid conditions.Keywords: type 2 diabetes mellitus, depression, stress, PHQ-9, SCQ, adiponectin, cortisol